Optimizing Corporate Social Responsibility Funds for Community Empowerment and Regional Planning in Urban Slums - Arifin Saleh; Mujahiddin Mujahiddin; Muhammad Daffa Gunawan (International Journal Reglement & Society (IJRS), 2022)
All companies engaged in various fields do not escape the obligation to implement Corporate Social Responsibility (CSR). The implementation of CSR is also an effort by the company to maintain and improve the company's good image and a way to maintain good relations with the community. The problem of community (community) empowerment is one of many problems that can be helped by the presence of CSR programs. Another problem is the emergence of urban slum areas. The purpose of writing this scientific paper is to find out and analyze the optimization of CSR funds for community empowerment and regional planning in urban slum areas. This paper is a literature review by conducting a study of previous research related to the writing that is being done. The result of this paper is that the optimization of CSR funds for community empowerment can be applied to funding assistance programs, skills training and other similar programs by taking into account the existing empowerment principles, so that the funds disbursed are right on target and have optimal impact on the community as recipients as well as companies as givers. In the regional planning sector in urban slum areas, CSR funds can be optimized through collaboration with the government through programs aimed at developing slum areas.